2021
DOI: 10.1080/09553002.2021.1864048
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNAs in regulating responses to radiotherapy in human breast cancer

Abstract: Breast cancer is the most common type of cancer that affects females globally. Radiotherapy is a standard treatment option for breast cancer, where one of its most significant limitations is radioresistance development. MicroRNAs (miRNAs) are small, non-protein-coding RNAs that have been widely studied for their roles as disease biomarkers. To date, several in vitro, in vivo, and clinical studies have reported the roles of miRNAs in regulating radiosensitivity and radioresistance in breast cancer cells. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 116 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…In the context of breast cancer, miRNAs have demonstrated their potential to modulate the cellular response to RT [ 87 ]. Certain miRNAs exert control over key proteins involved in DNA damage response and repair, thereby influencing the sensitivity of breast cancer cells to radiation [ 88 ].…”
Section: Crosstalk Between Mirnas and Cancer Progression During Rtmentioning
confidence: 99%
“…In the context of breast cancer, miRNAs have demonstrated their potential to modulate the cellular response to RT [ 87 ]. Certain miRNAs exert control over key proteins involved in DNA damage response and repair, thereby influencing the sensitivity of breast cancer cells to radiation [ 88 ].…”
Section: Crosstalk Between Mirnas and Cancer Progression During Rtmentioning
confidence: 99%
“…A recent review identified a variety of miRNAs as key players in regulating the sensitivity and resistance of breast cancer cells to radiotherapy. Notably, among 36 identified miRNAs impacting radio-responses, 22 were found to enhance radiosensitivity, 12 contributed to radioresistance, and 2 demonstrated both effects ( 24 ).…”
Section: Long Non-coding Rna and Micrornamentioning
confidence: 99%
“…In ovarian cancer (OC), miR-135a-3p, miR-200c, miR-216a and miR-340 can regulate the invasiveness of OC cells by regulating the epithelial-mesenchymal transition (EMT) program [ 82 , 83 , 84 , 85 ]. In addition, miRNAs are closely associated with the occurrence and development of many malignant tumors, such as lung cancer, pancreatic cancer and breast cancer [ 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Epigenetics In Cancer Occurrence and Cancer Radiotherapymentioning
confidence: 99%